A Tunable Amorphous Heteronuclear Iron and Cobalt Imidazolate Framework Analogue for Efficient Oxygen Evolution Reactions. Issue 8 (7th January 2021) - Zhao, Qingyun; Lin, Xiao; Zhou, Jing; Zhao, Chong; Zheng, Dehua; Song, Sanzhao; Jing, Chao; Zhang, Linjuan; Wang, Jian‐Qiang
Abstract: The structural diversity and tunable functionality of the amorphous metal‐organic frameworks (aMOFs) highlights this class of materials as a promising candidate for the development of sustainable energy technologies. The electrocatalytic performance in oxygen evolution reaction (OER) can be greatly improved by incorporating the hetero‐metallics into MOFs. Herein, the OER performance was significantly improved by the incorporation of Fe 3+ ions into the crystalline cobalt‐based MOF, leading to amorphous structure. Benefiting from the optimized surface morphology and electrochemical surface area, charge transport, was greatly facilitated. The Fe/Co aMOF with 1/4 ratio (labeled as AFC‐MOFs (1 : 4)) exhibited an excellent and stable OER activity, with an ultralow overpotential (256 mV at 10 mA cm −2 ) and Tafel slope of 42.7 mV dec −1 . XAS found that the majority of Co 2+ in AFC‐MOFs (1 : 4) is converted to low‐spin Co 3+ upon OER, while Fe 3+ is maintained during the OER process, supporting the synergistic catalytic mechanism between Fe and Co. This material outperforms benchmark IrO2, which could be attributed to the hollow amorphous structure and the optimized electronic properties. Abstract : A hollow‐structured FeCo‐cMOF electrocatalyst was developed for OER. Spectroscopic and microscopic studies demonstrated that the as‐prepared Fe/Co bimetallic MOF in 1/4 ratio of AFC to MOFs exhibits impressive OER activity, ascribed to its hollow, amorphous structure, which greatly increases the number of active sites, facilitating conversion of Co 2+ ion active sites to Co 3+ during the OER process.